Hygienic practice, microbial quality and physco-chemical properties of milk collected from farmers and market chains in Eastern Wollega zone of Sibu Sire districts, Ethiopia - Chala Adugna; Mitiku Eshetu (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
Thirty samples of fresh cow milk was taken from farmers immediately after milking and 15 milk samples was taken from market chains and analyzed for quality. From the sample about 31.08% were coagulate on clot on boiling test and 55.55% samples were coagulated on alcohol tests. Overall mean total bacterial counts, coliform and yeast and mould count were 5.74±0.10.65, 3.14±0.72 and 3.71±0.83 cfu/ml respectively and significantly different b/n producers source and markets channel source at (P<0.05). The highest total colony count was 6.77±1.1cfu/ml was observed at retailers. From the samples about 66.7% of the sample was in a normal range for specific gravity and 33.3% of the sample was not in a range of normal specific gravity. The overall mean of fat, protein, solid not fat were 4.65±0.50%, 3.67±0.05%, 8.78±0.15% respectively. In general the result indicated that milk samples collected from producers and market chains, were subjected to microbial contamination and does not meet the international milk quality standard. Therefore, adequate sanitary measures should be taken at all stages from production to consumer level.